Synergistic effect of single-atom Ag and hierarchical tremella-like g-C3N4: Electronic structure regulation and multi-channel carriers transport for boosting photocatalytic performance - Sun, Linlin; Feng, Yibing; Ma, Kai; Jiang, Xiaohan; Gao, Zhengyang; Wang, Jigang; Jiang, Nan; Liu, Xiaoshuo (Applied catalysis. B, Environmental, 2022)
It is significant to realize the synergistic effect of single-atom sites and its support to obtain excellent performance photocatalysts. Here, single-atom silver (SAAg) is embedded into the hierarchical tremella-like carbon nitride (3DT-CN) by an efficient one-step reduction method. The photo-degradation mechanism of SAAg/3DT-CN for tetracycline (TC) is first proposed. And the synergistic effect to improve photocatalytic activity is also discussed in depth. Density functional theory (DFT) calculations and physicochemical characterizations reveal that the synergistic effect of SAAg and 3DT-CN has improved the absorption capacity of visible light, the binding energy with oxygen, charge transfer behavior and other properties. Electron spin resonance (ESR) and capture experiments validate the active species involved in the reaction. The first-order kinetic constant of TC degradation by SAAg/3DT-CN is 8.4 times and 3.8 times that of 3DT-CN and AgNP/3DT-CN in 75 min, respectively. This work provides a meritorious structure-activity strategy for the removal of refractory antibiotics. [Display omitted] •The SAAg/3DT-CN photocatalyst is prepared by an efficient one-step reduction method.•Electronic structure regulation and multi-channel carrierstransportcan beachieved in SAAg/3DT-CN.•The synergistic effect mechanism of SAAgand 3DT-CN for tetracyclineis first proposed.•SAAg/3DT-CNhasexcellent charge separation efficiencyand visible light absorption capacity.•This work provides an economical and efficient technology to gain meritorious structure-activity materials.